Water: How Does It Influence the CaCO3 Formation?. Issue 5 (6th November 2019) - Du, Huachuan; Amstad, Esther
Abstract: Nature produces biomineral‐based materials with a fascinating set of properties using only a limited number of elements. This set of properties is obtained by closely controlling the structure and local composition of the biominerals. We are far from achieving the same degree of control over the properties of synthetic biomineral‐based composites. One reason for this inferior control is our incomplete understanding of the influence of the synthesis conditions and additives on the structure and composition of the forming biominerals. In this Review, we provide an overview of the current understanding of the influence of synthesis conditions and additives during different formation stages of CaCO3, one of the most abundant biominerals, on the structure, composition, and properties of the resulting CaCO3 crystals. In addition, we summarize currently known means to tune these parameters. Throughout the Review, we put special emphasis on the role of water in mediating the formation of CaCO3 and thereby influencing its structure and properties, an often overlooked aspect that is of high relevance. Abstract : The fascinating properties of biomineral‐based materials produced by nature have inspired much work dedicated to the formation of biominerals. The current understanding of the formation of CaCO3, one of the most abundant biominerals, is summarized in this Review with special emphasis on the role of water in mediating the formation of CaCO3, an often overlooked aspect that is of high relevance.